PERBANDINGAN PENGARUH HARGA MINYAK MENTAH TERHADAP INDEKS HARGA SAHAM PERUSAHAAN ENERGI DI INDONESIA DAN MALAYSIA SELAMA PERANG RUSSIA UKRAINA - Agustin, Isnaini Nuzula; Hesniati, Hesniati; Ellen, Ellen; Jasmine, Florentina; Vernando, Lovis; Kelvin, Kelvin; Vincent, Vincent (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
One of the world's largest consumption of energy is crude oil, which is a source of transportation fuel. Crude oil is often used as an indicator of the world economy because fluctuating oil prices can affect a country's capital market, both developed and developing countries. This study aims to analyze the comparison of the effect of crude oil prices on stock indexes in Indonesia and Malaysia during the RussiaUkraine War. This research is a comparative research using saturated sampling data collection method with a total sample of 454. The data is taken from index data listed on the Indonesian and Malaysian stock exchanges and world oil price data, then the data is tested using the Statistical Program for Social Science application. (SPSS). The results of this study indicate that the price of crude oil has a significant positive effect on the stock price index of Indonesian energy companies, while for Malaysia it produces a significant negative relationship.